2021
DOI: 10.1038/s41368-021-00119-3
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1-induced N-cadherin drives cell–cell communication through connexin43 in osteoblast lineage

Abstract: Gap junction (GJ) has been indicated to have an intimate correlation with adhesion junction. However, the direct interaction between them partially remains elusive. In the current study, we aimed to elucidate the role of N-cadherin, one of the core components in adhesion junction, in mediating connexin 43, one of the functional constituents in gap junction, via transforming growth factor-β1(TGF-β1) induction in osteoblasts. We first elucidated the expressions of N-cadherin induced by TGF-β1 and also confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Furthermore, we investigated if other cartilage-protective factors could prevent Cx43 reduction by TNFα. Anabolic factors, such as IGF, HGF, PDGF and TGF, have been shown to increase Cx43 expression in different tissues and cell types [ 29 , 30 , 31 , 32 , 33 ]. Among them, TGF-β1 action has been previously described in CH [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we investigated if other cartilage-protective factors could prevent Cx43 reduction by TNFα. Anabolic factors, such as IGF, HGF, PDGF and TGF, have been shown to increase Cx43 expression in different tissues and cell types [ 29 , 30 , 31 , 32 , 33 ]. Among them, TGF-β1 action has been previously described in CH [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…WCHSIRB-OT-2020-048). The cells used in the experiments were all isolated from C57BL/6J mice (1–3 days old) as previously described [ 65 , 66 ]. Immature chondrocytes isolated from epiphyseal hyaline cartilage were extracted from knee joints.…”
Section: Methodsmentioning
confidence: 99%
“…CDM scaffolds were novel culture systems for comparing the chondrogenesis of different stem cells under different culture conditions. 182 3D-Printed chitosan scaffold TGF-β3 and BMP6 Human infrapatellar fat pad adipose stem cells (IPFP-ASCs) 1. A cartilage-like matrix formed the top layer of a 3D-printed chitosan scaffold 2.…”
Section: Potential Therapeutic Roles Of Tgf-β3 In Osteoarthritis (Oa)mentioning
confidence: 99%
“…Several studies found synergy in the chondrogenic differentiation of ADSCs, bone marrow-derived mesenchymal stem cells (BMSCs), and periodontal ligament stem cells. 182 187 In addition, Yoo et al put forward an innovative idea, suggesting that a combination of TGF‑β3 and BMP6, which shows a synergistic effect on chondrogenesis, loaded into an efficient carrier such as exosomes, which themselves show a chondroprotective function, offers an effective approach to treat damaged cartilage in OA. 13 In addition to growth factors, agents such as heparin and HA enhance chondrogenesis when used in combination with TGF-β3.…”
Section: Potential Therapeutic Roles Of Tgf-β3 In Osteoarthritis (Oa)mentioning
confidence: 99%